Shell-making slurry for investment casting and preparation method thereof
By using a combination of modified powder and surfactant in the manufacturing of aircraft engine blades, the problem of poor stability of shell slurry is solved, and a slurry with high dispersion, suspension stability and coating is achieved, suitable for aviation Efficient manufacturing of engine blades.
Patent Information
- Application Number
- CN202411455990.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-14
AI Technical Summary
During the manufacturing process of aircraft engine blades, the poor stability of shell slurry, uneven coating and defects in the molded shell surface in investment casting affect the quality and manufacturing efficiency of molded shells.
A shell slurry including silica sol, modified zircon powder, modified cobalt aluminate powder, anionic surfactant, nonionic surfactant and defoaming agent is used to coat ethylene in situ on the surface of the powder. The copolymer of benzoic acid and vinyl phenol combines anionic and nonionic surfactants to improve powder dispersion and bonding properties, and prepares a slurry with high dispersion and excellent suspension stability.
It achieves high dispersion, suspension stability and coating properties of the slurry, stable retention rate of the slurry, long service life, suitable for large-piece casting on intelligent casting islands, and the preparation method is simple and industrialized.
Smart Images

Figure CN119304115A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of investment casting, and specifically relates to a shell-making slurry for investment casting with high dispersion, excellent suspension stability and coating properties, stable slurry retention rate and long service life, and a preparation method thereof. Background Art
[0002] Aircraft engine blades are one of the core components, and the quality of the blades is directly related to the main performance indicators of the entire aircraft engine. Therefore, the improvement of the key manufacturing technology of aircraft engine blades has always been a problem to be solved.
[0003] The manufacturing method of aircraft engine blades is often investment casting. Investment casting is very suitable for production in the form of smart casting islands. Investment casting, also known as lost wax casting or precision casting, is a near-net-shape forming technology that can mass-produce complex components in the form of smart casting islands. It is often used in the precision forming process of large, complex, thin-walled parts and cutting-edge core components. Compared with other casting methods and part processing and forming methods, it has many advantages: (1) The casting size is precise and the surface is smooth. The main advantages of investment castings are high dimensional accuracy and low surface roughness, which can greatly reduce the cutting allowance of castings; (2) Complex castings can be cast. Investment casting can cast castings with complex shapes and can also cast combined castings. It can maximize the similarity between the blank and the part and facilitate the structural design of the part; (3) It is not limited by alloy materials. Investment casting can be used for castings of various alloy materials, especially for alloy materials that are difficult to forge, weld or cut; (4) Improve the utilization rate of metal materials. Investment castings have small processing allowances and high metal utilization; (5) High production flexibility. Investment casting can be used for large-scale production, small-scale production, or even single-piece production.
[0004] Investment casting is a method of repeatedly dipping a refractory slurry on the surface of a fusible model, sanding and drying it layer by layer, heating and melting the investment pattern to form an integral shell, which is then subjected to high-temperature treatment and finally poured to obtain a casting.
[0005] Mold shell preparation is a key process step in investment casting. Generally, refractory materials and binders are prepared into stable slurry, which is then made into mold shell through a series of processes such as grouting, gelling, dewaxing and heat treatment. Among them, the key is to prepare shell making slurry with high dispersion, excellent suspension stability and coating properties, stable slurry retention rate and long service life.
[0006] The performance of shell slurry is a key factor affecting the quality of shell molds. In practice, problems such as poor stability of shell slurry, uneven slurry coating on the wax mold surface, and defects on the shell mold surface are often encountered. The above problems need to be solved urgently. Summary of the invention
[0007] The first object of the present invention is to provide a shell-making slurry for investment casting which has high dispersion, excellent suspension stability and coating properties, stable slurry retention rate and long service life.
[0008] The second object of the present invention is to provide a method for preparing the shell-making slurry.
[0009] Specifically, the present invention is implemented through the following technical solutions:
[0010] A shell-making slurry for investment casting, comprising, by weight, 100 parts of silica sol, 300-400 parts of modified zircon powder, 40-60 parts of modified cobalt aluminate powder, 1-1.5 parts of anionic surfactant, 1-1.5 parts of nonionic surfactant, 1-2 parts of defoaming agent and 30-40 parts of water;
[0011] The surface of the modified zircon powder is in-situ coated with a copolymer of vinyl benzoic acid and vinyl phenol;
[0012] The surface of the modified cobalt aluminate powder is in-situ coated with a copolymer of vinyl benzoic acid and vinyl phenol.
[0013] The content of silicon in the silica sol is 25-35 wt %.
[0014] In the copolymer of vinyl benzoic acid and vinyl phenol, the mass ratio of vinyl benzoic acid monomer to vinyl phenol monomer is 1:2-3.
[0015] The anionic surfactant includes sodium dodecylbenzene sulfonate or sodium diisooctyl sulfosuccinate;
[0016] The nonionic surfactant includes polyethylene glycol or Tween 80.
[0017] The defoaming agent includes n-butanol, n-octanol or polydimethylsiloxane.
[0018] The method for preparing the shell-making slurry for investment casting comprises the following steps:
[0019] S1: adding zircon powder into an organic solvent, and then adding vinyl benzoic acid, vinyl phenol and an initiator to react to obtain modified zircon powder;
[0020] S2: adding cobalt aluminate powder into an organic solvent, and then adding vinyl benzoic acid, vinyl phenol and an initiator to react to obtain modified cobalt aluminate powder;
[0021] S3: after mixing the modified zircon powder and the modified cobalt aluminate powder in water, an anionic surfactant and a defoaming agent are added to obtain slurry A; after mixing the silica sol with the nonionic surfactant, slurry B is obtained;
[0022] S4: Slurry A is mixed with slurry B to obtain shell-making slurry for investment casting.
[0023] The initiator includes azobisisobutyronitrile.
[0024] The organic solvent includes toluene.
[0025] The mass ratio of the zircon powder, vinyl benzoic acid, vinyl phenol and initiator is 100:5:10-15:3;
[0026] The mass ratio of the cobalt aluminate powder, vinyl benzoic acid, vinyl phenol and initiator is 100:5:10-15:3.
[0027] The reaction time is 10-30min;
[0028] The reaction temperature is 50-60°C.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The shell-making slurry for investment casting provided by the present invention has high dispersion, excellent suspension stability and coating properties, stable slurry retention rate, and long service life, and is suitable for casting large parts in an intelligent casting island.
[0031] The method for preparing the shell-making slurry for investment casting provided by the invention is simple and can be produced continuously and industrially. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A photograph showing the sedimentation of the shell-making slurry for investment casting prepared in Example 1 after standing for 1 hour;
[0033] Figure 2 A photograph showing the sedimentation of the shell-making slurry for investment casting prepared in Example 1 after standing for 2 hours;
[0034] Figure 3 A photograph showing the sedimentation of the shell-making slurry for investment casting prepared in Example 1 after standing for 3 hours;
[0035] Figure 4 A photograph showing the sedimentation of the shell-making slurry for investment casting prepared in Example 2 after standing for 1 hour;
[0036] Figure 5 A photograph showing the sedimentation of the shell-making slurry for investment casting prepared in Example 2 after standing for 2 hours;
[0037] Figure 6 A photograph showing the sedimentation of the shell-making slurry for investment casting prepared in Example 2 after standing for 3 hours;
[0038] Figure 7A flocculation photograph of the shell-making slurry for investment casting prepared in Comparative Example 1 is shown;
[0039] Figure 8 A flocculation photograph of the shell-making slurry for investment casting prepared in Comparative Example 2 is shown;
[0040] Fig. 9 A photograph showing the shell-making slurry for investment casting prepared in Comparative Example 3 that cannot be slurried;. DETAILED DESCRIPTION
[0041] The present invention provides a shell-making slurry for investment casting, which comprises, by weight, 100 parts of silica sol, 300-400 parts of modified zircon powder, 40-60 parts of modified cobalt aluminate powder, 1-1.5 parts of anionic surfactant, 1-1.5 parts of nonionic surfactant, 1-2 parts of defoaming agent and 30-40 parts of water; since silica sol is usually alkaline and negatively charged under alkaline conditions, when silica sol is used as a binder, in order to obtain a stably dispersed slurry, the powder in the silica sol should usually have a negative charge on its surface to stabilize the slurry. Since there are generally oxygen vacancies on the surface of zircon powder, the surface of the powder usually has a positive charge; at the same time, due to the phenomenon of hydrolysis, the cobalt aluminate powder is easy to adsorb positively charged ions under alkaline conditions, thereby being positively charged under alkaline conditions. Therefore, when the above-mentioned powder with a positive charge on the surface is dispersed in the silica sol, it is usually very easy to settle, and even causes the silica sol to flocculate. Therefore, coating the surface of the powder with negatively charged organic matter becomes a solution to this problem. Specifically, the present invention makes the surface of the powder negatively charged by in-situ coating the copolymer of vinyl benzoic acid and vinyl phenol on the surface of zircon powder; and in-situ coating the copolymer of vinyl benzoic acid and vinyl phenol on the surface of cobalt aluminate powder, thereby avoiding the flocculation of silica sol. However, after the copolymer of vinyl benzoic acid and vinyl phenol is coated on the surface of the powder, its surface potential is not high. Therefore, adding anionic surfactant can improve the surface potential of the powder, thereby improving the dispersion stability of the slurry. Since strong hydrogen bonds can be generated between carboxyl groups and silica sol, this will also lead to flocculation of silica sol. Therefore, adding nonionic surfactant can reduce the hydrogen bonds generated between carboxyl groups and silica sol. At the same time, since the hydrogen bonds generated between the phenolic hydroxyl groups connected to the benzene ring and the silica sol are also weak, the strength of the hydrogen bonds formed between the carboxyl groups and the silica sol can be reduced by copolymerization. Specifically, the silicon content in the silica sol is 25-35wt%.
[0042] Specifically, in the copolymer of vinyl benzoic acid and vinyl phenol, the mass ratio of vinyl benzoic acid monomer to vinyl phenol monomer is 1: 2-3. Within this ratio range, since the surface density of carboxyl groups is reduced by phenolic hydroxyl groups, the strength of the generated hydrogen bonds is also lower, so the silica sol is difficult to flocculate.
[0043] Specifically, the anionic surfactant may be sodium dodecylbenzenesulfonate or sodium diisooctyl sulfosuccinate; of course, it is obvious that other types of anionic surfactants may also be used.
[0044] Specifically, the nonionic surfactant is polyethylene glycol or Tween 80. Obviously, other types of nonionic surfactants may also be used.
[0045] Specifically, the defoaming agent is selected from n-butanol, n-octanol or polydimethylsiloxane.
[0046] The present invention also provides a method for preparing the shell slurry for investment casting, specifically, the method comprises the following steps: adding zircon powder and cobalt aluminate powder to an organic solvent respectively, and then adding vinyl benzoic acid and vinyl phenol and an initiator to react to obtain modified zircon powder;
[0047] Then, the modified zircon powder and the modified cobalt aluminate powder are mixed in water, and anionic surfactant and defoamer are added to obtain slurry A; the silica sol is mixed with nonionic surfactant to obtain slurry B; and then slurry A and slurry B are mixed to obtain shell-making slurry for investment casting. The purpose of mixing in this way is to make the nonionic surfactant adsorbed on the surface of the silica sol, so that after the modified zircon powder and the modified cobalt aluminate powder are added, it is difficult for the silica sol to form hydrogen bonds with the phenolic hydroxyl and carboxyl groups on the surface of the modified zircon powder and the modified cobalt aluminate powder.
[0048] Specifically, the initiator includes azobisisobutyronitrile. Other types of azo initiators may also be used.
[0049] Specifically, the organic solvent includes toluene.
[0050] Specifically, during in-situ coating, the organic matter cannot be too much, therefore, the mass ratio of the zircon powder, vinyl benzoic acid, vinyl phenol and initiator is 100:5:10-15:3;
[0051] Specifically, during in-situ coating, the amount of organic matter cannot be too much, therefore, the mass ratio of the cobalt aluminate powder, vinyl benzoic acid, vinyl phenol and initiator is 100:5:10-15:3.
[0052] Specifically, the reaction time is 10-30 minutes. When the reaction time is 10-30 minutes, the thickness of the organic matter on the surface of the powder will not be too large.
[0053] Specifically, the reaction temperature is 50-60°C.
[0054] The present invention is further described below in conjunction with specific embodiments. The parts in the specific embodiments are parts by weight.
[0055] Example 1
[0056] 100 parts of zircon powder were added to toluene, and then 5 parts of vinyl benzoic acid, 10 parts of vinyl phenol and 3 parts of azobisisobutyronitrile were added to react at 50° C. for 10 minutes to obtain modified zircon powder;
[0057] 100 parts of cobalt aluminate powder were added to toluene, and then 5 parts of vinyl benzoic acid, 10 parts of vinyl phenol and 3 parts of azobisisobutyronitrile were added to react at 50° C. for 10 minutes to obtain modified cobalt aluminate powder;
[0058] 300 parts of modified zircon powder and 40 parts of modified cobalt aluminate powder were mixed in 20 parts of water, and then 1 part of sodium dodecylbenzene sulfonate and 1 part of n-butanol were added to obtain slurry A. 100 parts of silica sol and 1 part of Tween 80 were mixed in 20 parts to obtain slurry B. Slurry A was mixed with slurry B to obtain shell-making slurry for investment casting.
[0059] Example 2
[0060] 100 parts of zircon powder were added to toluene, and then 5 parts of vinyl benzoic acid, 12 parts of vinyl phenol and 3 parts of azobisisobutyronitrile were added to react at 50° C. for 10 minutes to obtain modified zircon powder;
[0061] 100 parts of cobalt aluminate powder were added to toluene, and then 5 parts of vinyl benzoic acid, 12 parts of vinyl phenol and 3 parts of azobisisobutyronitrile were added to react at 50° C. for 10 minutes to obtain modified cobalt aluminate powder;
[0062] 300 parts of modified zircon powder and 40 parts of modified cobalt aluminate powder were mixed in 20 parts of water, and then 1 part of sodium dodecylbenzene sulfonate and 1 part of n-butanol were added to obtain slurry A; 100 parts of silica sol and 1 part of Tween 80 were mixed in 20 parts of water to obtain slurry B;
[0063] Slurry A and slurry B are mixed to obtain a shell-making slurry for investment casting.
[0064] Example 3
[0065] 100 parts of zircon powder were added to toluene, and then 5 parts of vinyl benzoic acid, 15 parts of vinyl phenol and 3 parts of azobisisobutyronitrile were added to react at 50° C. for 10 minutes to obtain modified zircon powder;
[0066] 100 parts of cobalt aluminate powder were added to toluene, and then 5 parts of vinyl benzoic acid, 15 parts of vinyl phenol and 3 parts of azobisisobutyronitrile were added to react at 50° C. for 10 minutes to obtain modified cobalt aluminate powder;
[0067] 300 parts of modified zircon powder and 40 parts of modified cobalt aluminate powder were mixed in 20 parts of water, and then 1 part of sodium dodecylbenzene sulfonate and 1 part of n-butanol were added to obtain slurry A; 100 parts of silica sol and 1 part of Tween 80 were mixed in 20 parts of water to obtain slurry B;
[0068] Slurry A and slurry B are mixed to obtain a shell-making slurry for investment casting.
[0069] Example 4
[0070] 100 parts of zircon powder were added to toluene, and then 5 parts of vinyl benzoic acid, 12 parts of vinyl phenol and 3 parts of azobisisobutyronitrile were added to react at 50° C. for 10 minutes to obtain modified zircon powder;
[0071] 100 parts of cobalt aluminate powder were added to toluene, and then 5 parts of vinyl benzoic acid, 12 parts of vinyl phenol and 3 parts of azobisisobutyronitrile were added to react at 50° C. for 10 minutes to obtain modified cobalt aluminate powder;
[0072] 400 parts of modified zircon powder and 40 parts of modified cobalt aluminate powder were mixed in 20 parts of water, and 1.5 parts of sodium dodecylbenzene sulfonate and 2 parts of n-butanol were added to obtain slurry A; 100 parts of silica sol and 1.5 parts of Tween 80 were mixed in 20 parts of water to obtain slurry B;
[0073] Slurry A and slurry B are mixed to obtain a shell-making slurry for investment casting.
[0074] Example 5
[0075] 100 parts of zircon powder were added to toluene, and then 5 parts of vinyl benzoic acid, 10 parts of vinyl phenol and 3 parts of azobisisobutyronitrile were added to react at 50° C. for 10 minutes to obtain modified zircon powder;
[0076] 100 parts of cobalt aluminate powder were added to toluene, and then 5 parts of vinyl benzoic acid, 10 parts of vinyl phenol and 3 parts of azobisisobutyronitrile were added to react at 50° C. for 10 minutes to obtain modified cobalt aluminate powder;
[0077] 300 parts of modified zircon powder and 40 parts of modified cobalt aluminate powder were mixed in 20 parts of water, and then 1 part of sodium dodecylbenzene sulfonate and 1 part of n-butanol were added to obtain slurry A; 100 parts of silica sol and 1 part of Tween 80 were mixed in 20 parts of water to obtain slurry B;
[0078] Slurry A and slurry B are mixed to obtain a shell-making slurry for investment casting.
[0079] Example 6
[0080] 100 parts of zircon powder were added to toluene, and then 5 parts of vinyl benzoic acid, 10 parts of vinyl phenol and 3 parts of azobisisobutyronitrile were added to react at 50° C. for 10 minutes to obtain modified zircon powder;
[0081] 100 parts of cobalt aluminate powder were added to toluene, and then 5 parts of vinyl benzoic acid, 10 parts of vinyl phenol and 3 parts of azobisisobutyronitrile were added to react at 50° C. for 10 minutes to obtain modified cobalt aluminate powder;
[0082] 300 parts of modified zircon powder and 60 parts of modified cobalt aluminate powder were mixed in 20 parts of water, and then 1.5 parts of sodium diisooctyl sulfosuccinate and 2 parts of polydimethylsiloxane were added to obtain slurry A; 100 parts of silica sol and 1.5 parts of polyethylene glycol were mixed in 20 parts to obtain slurry B;
[0083] Slurry A and slurry B are mixed to obtain a shell-making slurry for investment casting.
[0084] Comparative Example 1
[0085] 100 parts of zircon powder were added to toluene, and then 5 parts of vinyl benzoic acid and 3 parts of azobisisobutyronitrile were added and reacted at 50°C for 10 minutes to obtain modified zircon powder;
[0086] 100 parts of cobalt aluminate powder were added to toluene, and then 5 parts of vinyl benzoic acid and 3 parts of azobisisobutyronitrile were added to react at 50° C. for 10 minutes to obtain modified cobalt aluminate powder;
[0087] 300 parts of modified zircon powder and 40 parts of modified cobalt aluminate powder were mixed in 20 parts of water, and then 1 part of sodium dodecylbenzene sulfonate and 1 part of n-butanol were added to obtain slurry A. 100 parts of silica sol and 1 part of Tween 80 were mixed in 20 parts to obtain slurry B. Slurry A was mixed with slurry B to obtain shell-making slurry for investment casting.
[0088] Comparative Example 2
[0089] 100 parts of zircon powder were added to toluene, and then 5 parts of vinyl benzoic acid, 10 parts of vinyl phenol and 3 parts of azobisisobutyronitrile were added to react at 50° C. for 10 minutes to obtain modified zircon powder;
[0090] 100 parts of cobalt aluminate powder were added to toluene, and then 5 parts of vinyl benzoic acid, 10 parts of vinyl phenol and 3 parts of azobisisobutyronitrile were added to react at 50° C. for 10 minutes to obtain modified cobalt aluminate powder;
[0091] 300 parts of modified zircon powder, 40 parts of modified cobalt aluminate powder, 1 part of n-butanol, 100 parts of silica sol and 1 part of Tween 80 were mixed in 40 parts to obtain a shell-making slurry for investment casting.
[0092] Comparative Example 3
[0093] 300 parts of zircon powder and 40 parts of cobalt aluminate powder were mixed in 20 parts of water, and then 1 part of sodium dodecylbenzene sulfonate and 1 part of n-butanol were added to obtain slurry A; 100 parts of silica sol and 1 part of Tween 80 were mixed in 20 parts to obtain slurry B;
[0094] Slurry A and slurry B are mixed to obtain a shell-making slurry for investment casting.
[0095] Comparative Example 4
[0096] 300 parts of zircon powder and 40 parts of cobalt aluminate powder were mixed in 20 parts of water, and 1 part of n-butanol was added to obtain slurry A; 100 parts of silica sol and 1 part of Tween 80 were mixed in 20 parts of water to obtain slurry B;
[0097] Slurry A and slurry B are mixed to obtain a shell-making slurry for investment casting.
[0098] Completely immerse the cleaned wax sheet (20mmx40mmx1mm) into the prepared slurry. Weigh the weight before and after immersion in the slurry. Calculate the slurry retention rate R and coating thickness H according to the following formula.
[0099] R=(WW,) / S
[0100]
[0101] Where R is the retention rate, Wp is the mass of the wax flake before slurry dipping, g; Wd is the mass of the wax flake after slurry dipping, g; S is the surface area of the wax flake, cm 2 ; D is the density of the slurry, g / cm 2 .
[0102] The retention rates of the shell-making slurries prepared in the examples and comparative examples are as follows:
[0103] Retention rate (%) Example 1 24 Example 2 22 Example 3 25 Example 4 26 Example 5 24 Example 6 24 Comparative Example 1 12 Comparative Example 2 10 Comparative Example 3 9 Comparative Example 4 5
Claims
1. A shell-making slurry for investment casting, characterized in that: In parts by weight, it comprises 100 parts of silica sol, 300-400 parts of modified zircon powder, 40-60 parts of modified cobalt aluminate powder, 1-1.5 parts of anionic surfactant, 1-1.5 parts of nonionic surfactant, 1-2 parts of defoaming agent and 30-40 parts of water; The surface of the modified zircon powder is in-situ coated with a copolymer of vinyl benzoic acid and vinyl phenol; The surface of the modified cobalt aluminate powder is in-situ coated with a copolymer of vinyl benzoic acid and vinyl phenol.
2. The shell-making slurry for investment casting according to claim 1, characterized in that: The content of silicon in the silica sol is 25-35 wt %.
3. The shell-making slurry for investment casting according to claim 1, characterized in that: In the copolymer of vinyl benzoic acid and vinyl phenol, the mass ratio of vinyl benzoic acid monomer to vinyl phenol monomer is 1:2-3.
4. The shell-making slurry for investment casting according to claim 1, characterized in that: The anionic surfactant includes sodium dodecylbenzene sulfonate or sodium diisooctyl sulfosuccinate; The nonionic surfactant includes polyethylene glycol or Tween 80.
5. The shell-making slurry for investment casting according to claim 1, characterized in that: The defoaming agent includes n-butanol, n-octanol or polydimethylsiloxane.
6. The method for preparing shell-making slurry for investment casting according to claim 1, characterized in that: The steps include: S1: adding zircon powder into an organic solvent, and then adding vinyl benzoic acid, vinyl phenol and an initiator to react to obtain modified zircon powder; S2: adding cobalt aluminate powder into an organic solvent, and then adding vinyl benzoic acid, vinyl phenol and an initiator to react to obtain modified cobalt aluminate powder; S3: after mixing the modified zircon powder and the modified cobalt aluminate powder in water, an anionic surfactant and a defoaming agent are added to obtain slurry A; after mixing the silica sol with the nonionic surfactant, slurry B is obtained; S4: Slurry A is mixed with slurry B to obtain shell-making slurry for investment casting.
7. The method for preparing shell-making slurry for investment casting according to claim 1, characterized in that: The initiator includes azobisisobutyronitrile.
8. The method for preparing shell-making slurry for investment casting according to claim 1, characterized in that: The organic solvent includes toluene.
9. The method for preparing shell-making slurry for investment casting according to claim 1, characterized in that: The mass ratio of the zircon powder, vinyl benzoic acid, vinyl phenol and initiator is 100:5:10-15:3; The mass ratio of the cobalt aluminate powder, vinyl benzoic acid, vinyl phenol and initiator is 100:5:10-15:
3.
10. The method for preparing shell-making slurry for investment casting according to claim 1, characterized in that: The reaction time is 10-30min; The reaction temperature is 50-60°C.